2021
DOI: 10.3389/fneur.2020.610318
|View full text |Cite
|
Sign up to set email alerts
|

The Hemoglobin, Albumin, Lymphocyte, and Platelet (HALP) Score Is Associated With Poor Outcome of Acute Ischemic Stroke

Abstract: Background: The combined index of hemoglobin, albumin, lymphocyte, and platelet (HALP) is considered a novel score to reflect systemic inflammation and nutritional status. This study aimed to investigate the association between HALP score and poor outcome in patients with acute ischemic stroke (AIS).Methods: Consecutive AIS patients within 24 h after onset were prospectively enrolled. Poor outcome was a combination of a new stroke event (ischemic and hemorrhagic) and all-cause death within 90 days and 1 year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 34 publications
2
52
0
1
Order By: Relevance
“…In this index, the general well-being of the patient is assessed based on hemoglobin, albumin, lymphocyte, and platelet values. A high HALP score is associated with longer survival (8,11,13). Anemia is a common condition in intensive care patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this index, the general well-being of the patient is assessed based on hemoglobin, albumin, lymphocyte, and platelet values. A high HALP score is associated with longer survival (8,11,13). Anemia is a common condition in intensive care patients.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al (19) stated that HALP score was an independent prognostic index in patients with esophageal cancer. Tian et al (11) showed that HALP score was associated with 90-day and 1-year mortality in patients with stroke. Xu et al (13) stated that HALP score was a good predictor of postoperative survival and recurrence in patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These immune cells exacerbate the injury by releasing additional inflammatory factors, such as ROS, MMP-9, and neutrophil elastase, which are prominent effectors of BBB disruption [17]. It also has been shown that most AIS patients course some degree of immune dysregulation; however, when these mechanisms are overstimulated worsen short and long-term clinical outcomes are expected [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Patients enrolled in the study were from the database of the Henan Province Stroke Registry ( 14 16 ) at the First Affiliated Hospital of Zhengzhou University from January 2015 to December 2018. AIS was diagnosed according to criteria defined by the World Health Organization ( 17 ) based on neuroimaging results, patient history, and clinical data.…”
Section: Methodsmentioning
confidence: 99%